Effect of ontology patterns on RDF query balancing - Šiška, Petr; Svátek, Vojtěch, 1967 prosinec 1.-; Kučera, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The master thesis deals with the effect of ontology patterns on RDF query balancing. This thesis aims to provide a new perspective on the impact of using ontology patterns to model RDF data with a combination of load balancing methods. By analyzing three ontology patterns in detail, the study sheds light on the correlation between ontology patterns and query load, offering valuable insights for decision-making in RDF data modeling. The research also delves into modern load balancing methods in RDF querying and presents the influence of the ontology pattern using these methods on overall query balancing. The work highlighted the most important findings that can help in future data modeling in RDF.
Vedoucí práce: Vojtěch Svátek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses